1987
DOI: 10.2527/jas1987.641247x
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Luteinizing Hormone and Follicle Stimulating Hormone in Intact and Ovariectomized Mares in Summer and Winter

Abstract: Sequential samples of blood were drawn via jugular catheters every 15 min for 24 h from four mares in each of five reproductive states: intact anestrous mares in winter, intact diestrous mares in summer, intact estrous mares in summer, ovariectomized mares in winter and ovariectomized mares in summer. Estrous mares were sampled on d 4 or 5 of estrus and diestrous mares on d 10 or 11 of diestrus. Each sample of plasma was assessed for concentrations of luteinizing hormone (LH) and follicle stimulating hormone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…2·89 to 3·45 mg/day per mare). In 400-500 kg body weight cyclic mares, these rates were lower, ranging from 0·84 to 2·6 mg/day (Irvine 1979) which is consistent with the fact that plasma concentrations of FSH are from three to four times lower in cyclic than in ovariectomized mares (Freedman et al 1979, Thompson et al 1987.…”
Section: Use Of Kinetic Studies To Determine a Dosage Regimen For Efsmentioning
confidence: 66%
See 2 more Smart Citations
“…2·89 to 3·45 mg/day per mare). In 400-500 kg body weight cyclic mares, these rates were lower, ranging from 0·84 to 2·6 mg/day (Irvine 1979) which is consistent with the fact that plasma concentrations of FSH are from three to four times lower in cyclic than in ovariectomized mares (Freedman et al 1979, Thompson et al 1987.…”
Section: Use Of Kinetic Studies To Determine a Dosage Regimen For Efsmentioning
confidence: 66%
“…This dosage regimen corresponded to the maximal daily production rate that we determined in ovariectomized pony mares. This dose was also expected to supply approximately 300% of the amount of eFSH produced in cyclic mares (Freedman et al 1979, Thompson et al 1987. As the results of this first trial gave satisfactory ovarian stimulation but undesirable side effects, a second trial (trial 2) was performed with a dose divided by 2: 1·72 mg eFSH per mare (2·2 µg/kg three times a day).…”
Section: Kinetic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…How day length and its melatonin signal are translated into a change in GnRH pulse generator activity is unknown. In the seasonally anestrous mare, investigators have shown that LH and FSH pulse frequency is very low [Fitzgerald et al, 1987;Thompson et al, 1987], but that it gradually increases together with the LH:FSH ratio as the mare makes the transition into the breeding season . On the other hand, the termination of the breeding season is marked by failure of preovulatory follicles to ovulate; this implies inadequate LH, possibly due to failure to increase GnRH pulse generator activity following luteolysis [Snyder et al, 1979].…”
Section: Control Of Seasonal Breedingmentioning
confidence: 99%
“…2) and 1-4 times daily during diestrus (Fig. 3) [Thompson et al, 1987;; and in these states, daily samples or brief windows of peripheral blood sampling are inadequate to describe the cyclic secretory patterns of both gonadotropins.…”
Section: Pulsatilitymentioning
confidence: 99%